Attention, flexibility, and imagery in misophonia: Does attention exacerbate everyday disliking of sound?. Issue 10 (26th November 2021) - Simner, J.; Koursarou, S.; Rinaldi, L.J.; Ward, J.
ABSTRACT: Introduction: Misophonia is an unusually strong aversion to everyday sounds, such as chewing, crunching, or breathing. Here, we ask whether misophonia might be tied to an unusual profile of attention (and related traits), which serves to substantially heighten an otherwise everyday disliking of sounds. Methods: In Study 1, we tested 136 misophonics and 203 non-misophonics on self-report measures of attention to detail, cognitive inflexibility, and auditory imagery, as well as collecting details about their misophonia. In Study 2, we administered the Embedded Figures task to 20 misophonics and 36 non-misophonics. Results: We first showed that the degree to which sounds trigger misophonia reflects the pattern by which they are (more mildly) disliked by everyone. This suggests that misophonia is scaffolded onto existing mechanisms rather than qualitatively different ones. Compared to non-misophonics, we also found that misophonics self-reported greater attention to detail, cognitive inflexibility, and auditory imagery. As their symptoms worsen, they also become more accurate in an attentional task (Embedded Figures). Conclusions: Our findings provide a better understanding of misophonia and support the hypothesis that dispositional traits of attention to detail may be key to elevating everyday disliking of sound into the more troubling aversions of misophonia.